2022
DOI: 10.1101/2022.05.23.493113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Derivation of the immortalized cell line-UM51-PrePodo-hTERT and its responsiveness to Angiotensin II and activation of RAAS

Abstract: Recent demographic studies predict there will be a considerable increase of elderly people within the next decades. Aging has been recognized as one of the main risk factors of the world's most prevalent diseases, including neurodegenerative disorders, cancer, cardiovascular disease, and metabolic disease. During the process of aging a gradual loss of tissue volume and organ function is observed, which is partially caused by replicative senescence. The capacity of cellular proliferation and replicative senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, another study carried out by Pierzchalski et al, showed that p53 is able to induce apoptosis via the activation of the Renin-Angiotensin System 29 . In two recent studies carried out in our laboratory, we demonstrated the devastating effect of the activated Renin-Angiotensin-System on podocyte morphology and functionality 51,52 . Therefore, we propose that the observed upregulated secretion of EGFR and VEGF mainly trigger angiogenesis and the activation of p53 and the Renin-Angiotensin system.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, another study carried out by Pierzchalski et al, showed that p53 is able to induce apoptosis via the activation of the Renin-Angiotensin System 29 . In two recent studies carried out in our laboratory, we demonstrated the devastating effect of the activated Renin-Angiotensin-System on podocyte morphology and functionality 51,52 . Therefore, we propose that the observed upregulated secretion of EGFR and VEGF mainly trigger angiogenesis and the activation of p53 and the Renin-Angiotensin system.…”
Section: Discussionmentioning
confidence: 88%